Bibliography on the subject of sustainable water resources management and transformation. - Scheele, Ulrich (My University, 2009)
Bibliographie zum Thema nachhaltige Wasserwirtschaft und nachhaltiges Wassermanagement. Ausgewertet wurde Literatur der Jahre 2002 bis 2009. Von den Referenzen wird, sofern vorhanden direkt auf online-Quellen verwiesen. Ausserdem ist jeder Literaturstelle mit einer geographischen Zuordnung versehen.

A comprehensive analysis of the literature was made. Databases specific to this subject, relevant professional journals, official documents and "gray" literature were examined fore this purpose. The evaluation was restricted to contributions since the year 2002 from industrial countries. The restriction in time is due to the fact that this special debate about the future of infrastructure was only initiated at the beginning of this century; the geographical restriction arises from the interest in being able to utilise these experiences for the situation in the Federal Republic of Germany. The present report includes a summary of the literature evaluated. Besides the bibliographic information, for each reference the principal geographical area in which the work was carried out is given. To the extent available, the Internet sources are also given. Reference is made either directly to the relevant document or to the organisation publishing the document. Viewing the international literature addressing the topic of models and practical projects for the transformation of water infrastructure, it emerges that a few essential driving forces can be seen as the decisive factors: Sustainable development / Climatic change / New technologies / Demographic change / Urban regeneration projects / Integration of infrastructure and spatial planning. This differentiation was also used for summarising the literature.
Keywords: Versorgung; Wasserwirtschaft; Wasserversorgung; Trinkwasser; Wasserverteilung; Wasserqualität; Wasserschutz; Abwasser; Technische Infrastruktur; Bibliographie; Nachhaltigkeit